Discourses and images of violence - Marquetti, Fernanda Cristina; Adorno, Rubens Camargo Ferreira (Saúde e Sociedade, 2014)
This article was based of the Ph.D research “Discourses and Images of Violence” in which we discuss violent deaths (homicides) in the São Paulo metropolis, favoring the study of cultural and psychic elaborations that happen around this phenomenon. The main objective of this research was to address two types of violent deaths discourses. The discourse of a population submitted to the event of violent death and the discourse of the televised media about the violence phenomenon. There are two approaches in the methodology of this research. The first one is an ethnographic approach to as seen as a violent territory in the city of São Paulo. The second one refers to two analysis of violent deaths discourses: televised media and narratives of the territory residents. The ethnographic results of the violent territory found in the sociability strand, distress, fear, survival strategies and other excuses to live in a violent neighborhood. In the resident narratives we find a series of fragmented verbal discourses, chaotic, not organized were the terror to excessive closeness to death was present. On the other hand, analyzing the discourse of the televised media, we find an excess of images, verbalizations, theories and interpretations about violence.